Keniscayaan Merintis Program Kreatif Produktif Di Usia Tua Desa Tegalsari Kecamatan Plered Kabupaten Cirebon - Citra Lela; Cory Vidiati; Kharimah Kharimah; Mamba’atul Hilmi; Meyfa Dwi Hana Anindya; Muzdhalifah Muzdhalifah (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This paper was prepared as a contribution from KPM students of Bunga Bangsa Islamic University Cirebon who are concerned about the welfare of elderly. The paradigm that the elderly population is not economically productive and often suffers from various diseases has become a special concern for students in community service programs. Various activities are carried out to stimulate the fine and gross motor skills of the elderly, which at the same time proves that they need attention and appreciation from society, family, and the state. The implications of this community service program are very positive for the elderly in Tegalsari Village, Plered District, Cirebon Regency. Although there are time constraints in program implementation, this can be overcome by creating successor cadres. overcome by creating successor cadres who are able to continue the program. Thus, the benefits can be felt sustainably by the elderly community in the village. Students hope that this effort will not only improve the welfare of the elderly but also build community awareness of the importance of their role and support. Through this service, it is hoped that a society that cares more and appreciates the existence of the elderly as an important part of the community will be realized